2020
DOI: 10.1186/s40478-020-01072-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic analyses uncover APOE-mediated regulation of brain and cerebrospinal fluid beta-amyloid levels in Parkinson disease

Abstract: Alpha-synuclein is the main protein component of Lewy bodies, the pathological hallmark of Parkinson’s disease. However, genetic modifiers of cerebrospinal fluid (CSF) alpha-synuclein levels remain unknown. The use of CSF levels of amyloid beta1–42, total tau, and phosphorylated tau181 as quantitative traits in genetic studies have provided novel insights into Alzheimer’s disease pathophysiology. A systematic study of the genomic architecture of CSF biomarkers in Parkinson’s disease has not yet been conducted.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 73 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Several studies have examined the associations between PD PRS and these CSF biomarkers. Two studies conducted by Ibanez et al, [24,52], and one study by Li et al [25] did not find an association between PRS and CSF α-syn, while Lee et al [53] found that higher PD PRS was associated with lower CSF α-syn. Notably, Ibanez et al [52] found that PD PRS was correlated with CSF Aβ42 and PD cases with higher PRS present lower CSF Aβ42 levels, indicating that PD development and accumulation of Aβ42 in the brain may share similar pathways.…”
Section: Prs and Biomarkersmentioning
confidence: 95%
“…Several studies have examined the associations between PD PRS and these CSF biomarkers. Two studies conducted by Ibanez et al, [24,52], and one study by Li et al [25] did not find an association between PRS and CSF α-syn, while Lee et al [53] found that higher PD PRS was associated with lower CSF α-syn. Notably, Ibanez et al [52] found that PD PRS was correlated with CSF Aβ42 and PD cases with higher PRS present lower CSF Aβ42 levels, indicating that PD development and accumulation of Aβ42 in the brain may share similar pathways.…”
Section: Prs and Biomarkersmentioning
confidence: 95%
“…Specifically, TaqMan assays (Applied Biosystems, Waltham, MA) for rs429358 (ABI#C_3084793_20) and rs7412 (ABI#C_904973_10) were used, as we previously published. 34 ABI Sequence Detection software was used to detect the 6 combinations of APOE e2, e3, and e4.…”
Section: Apoe Genotypingmentioning
confidence: 99%